2015
DOI: 10.1186/s12889-015-2463-1
|View full text |Cite
|
Sign up to set email alerts
|

The current status of malaria epidemiology in Bolifamba, atypical Cameroonian rainforest zone: an assessment of intervention strategies and seasonal variations

Abstract: BackgroundGlobal malaria has been on the decline over the past decade due to expansion of interventions. The present study aimed at determining the current status of malaria epidemiology in the context of sustained interventions and seasonal variations in Bolifamba, which represents a typical semi-urban malaria endemic community in the Cameroonian rainforest.MethodsA monthly cross-sectional survey was carried out in Bolifamba, a multi ethnic semi-urban locality on the eastern flanks of Mt Cameroon, for a year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(27 reference statements)
1
11
6
Order By: Relevance
“…However, the prevalence is lower than the 66.9% reported earlier in children ≤ 14 in Tole community [ 27 ] and the 45.3% in pupils between 4 and 16 years in other areas in the Mount Cameroon area [ 2 ]. Even though a lower prevalence has been reported by Apinjoh et al [ 5 ] and Nyasa et al [ 36 ] in the Mount Cameroon area, the GMPD observed in the study (413 parasites/µL of blood) is lower than the 1721 parasites/µL of blood reported by Apinjoh et al [ 5 ]. Although, the Mount Cameroon area has an equatorial climate characterized by abundant rainfall and constant humidity which are factors favouring intense and perennial transmission of the malaria parasite [ 37 ], the decrease in malaria morbidity is thought to be the result of sustained control measures including implementation of long lasting insecticide nets and use of artemisinin-based combination therapy (ACT) as recommended by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 80%
“…However, the prevalence is lower than the 66.9% reported earlier in children ≤ 14 in Tole community [ 27 ] and the 45.3% in pupils between 4 and 16 years in other areas in the Mount Cameroon area [ 2 ]. Even though a lower prevalence has been reported by Apinjoh et al [ 5 ] and Nyasa et al [ 36 ] in the Mount Cameroon area, the GMPD observed in the study (413 parasites/µL of blood) is lower than the 1721 parasites/µL of blood reported by Apinjoh et al [ 5 ]. Although, the Mount Cameroon area has an equatorial climate characterized by abundant rainfall and constant humidity which are factors favouring intense and perennial transmission of the malaria parasite [ 37 ], the decrease in malaria morbidity is thought to be the result of sustained control measures including implementation of long lasting insecticide nets and use of artemisinin-based combination therapy (ACT) as recommended by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition, it is higher than the 59.7% reported in pre-school children in Gaza Strip-Palestine [29] and the 54% reported in internally displaced children in Edo-Nigeria [30]. While the prevalence of malaria parasite in this population is lower than previously reported in children < than 5 years [10,31,32], that of anaemia has experienced an increase. The surge in prevalence of anaemia which is an important outcome indicator of poor nutrition and health may reflect the living conditions, poverty and increase in food EBF Exclusive breastfeeding, MF Mixed feeding, NBF No breast feeding.…”
Section: Discussionmentioning
confidence: 55%
“…Studies conducted in the South-West region after LLINs mass campaigns scale-up, on children aged one month to 14 years-old, indicated a prevalence varying from 9 to 41.5% ( n = 454) during the rainy season in Tiko, Limbé, Idenau, Mutengene and Buéa [18, 68, 70–75]. High parasite prevalence varying from 41.7 to 56.2% ( n = 828) along the slope of Mount Cameroon was also recorded [76, 77]. The social crisis affecting the North-West and South-West regions of the country with a displaced population, could be affecting malaria epidemiology in the area and this could constitute an enormous challenge that could impede malaria elimination or control efforts in these regions and neighbouring regions.…”
Section: Situation Of Malaria In Cameroonmentioning
confidence: 99%